Is our life sustainable? - Ramos Sancha, Javier; CEDEC (Centro Nacional de Desarrollo Curricular en Sistemas no Propietarios) (2021)
Welcome to a new learning adventure in which we are going to improve our Sicence skills and your ICT ones, also we are going to learn some English skills. This project is about the your energy, what the different types of energy are and how we can be sustainable with the use of energy in our daily lifes. Try to do your best and to enjoy your learning process.
LMH, 5. eta 6. mailak
Keywords: Baliabide digitalak; Curriculumeko baliabideak; Eduki digital didaktikoak; Erronketan oinarritutako ikaskuntza